Emergency Remote Learning in Nursing Education During the COVID-19 Pandemic - Jeon Eunjoo; Peltonen Laura-Maria; Block Lorraine; Ronquillo Charlene; Tayaben Jude L.; Nibber Raji; Pruinelli Lisiane; Perezmitre Erika Lozada; Sommer Janine; Topaz Maxim; Eler Gabrielle Jacklin; Shishido Henrique Yoshikazu; et al. (Netherlands, 2022)
Due to the corona (COVID-19) pandemic, several countries are currently conducting non-face-to-face education. Therefore, teachers of nursing colleges have been carrying out emergency remote education. This study developed a questionnaire to understand the status of Emergency Remote Learning (ERL) in nursing education internationally, translated it into 7 languages, and distributed it to 18 countries. A total of 328 nursing educators responded, and the most often used online methods were Social networking technology such as Facebook, Google+ and Video sharing platform such as YouTube. The ERL applied to nursing education was positively evaluated as 3.59 out of 5. The results of the study show that during the two semesters nursing college professors have well adapted to this unprecedent crisis of teaching. The world after COVID-19 has become a completely different place, and nursing education should be prepared for ‘untact’ education.
Public Health and Informatics: Proceedings of MIE 2021